Maize 9-Lipoxygenase ZmLOX3 Controls Development, Root-Specific Expression of Defense Genes, and Resistance to Root-Knot Nematodes - Xiquan Gao; James Starr; Cornelia Göbel; Jürgen Engelberth; Ivo Feussner; James Tumlinson; Michael Kolomiets (Molecular Plant-Microbe Interactions, 2008)
Root-knot nematodes (RKN) are severe pests of maize. Although lipoxygenase (LOX) pathways and their oxylipin products have been implicated in plant–nematode interactions, prior to this report there was no conclusive genetic evidence for the function of any plant LOX gene in such interactions. We showed that expression of a maize 9-LOX gene, ZmLOX3, increased steadily and peaked at 7 days after inoculation with Meloidogyne incognita RKN. Mu-insertional lox3-4 mutants displayed increased attractiveness to RKN and an increased number of juveniles and eggs. A set of jasmonic acid (JA)- and ethylene (ET)-responsive and biosynthetic genes as well as salicylic acid (SA)-dependent genes were overexpressed specifically in the roots of lox3-4 mutants. Consistent with this, levels of JA, SA, and ET were elevated in lox3-4 mutant roots, but not in leaves. Unlike wild types, in lox3-4 mutant roots, a phenylalanine ammonia lyase (PAL) gene was not RKN-inducible, suggesting a role for PAL-mediated metabolism in nematode resistance. In addition to these alterations in the defense status of roots, lox3-4 knockout mutants displayed precocious senescence and reduced root length and plant height compared with the wild type, suggesting that ZmLOX3 is required for normal plant development. Taken together, our data indicate that the ZmLOX3-mediated pathway may act as a root-specific suppressor of all three major defense signaling pathways to channel plant energy into growth processes, but is required for normal levels of resistance against nematodes.